Diagnostic performance of contrast-enhanced T2-FLAIR MRI in the detection of meningitis - Sanjay P.; Vittal Manohar; Sushmita Balol; Yashwanth Naik M.B. (South African Journal of Radiology)
Background: The contrast-enhanced T2-FLAIR (CE-T2-FLAIR) sequence on MRI, through the suppression of CSF and vascular signals, can detect subtle meningeal enhancement in meningitis that may not be appreciable on the routinely used contrast-enhanced T1W (CE-T1W) sequence.